Efeito da presença, tipo e da cor da roupa sobre a velocidade em 10km de corrida sob o sol - Diego de Alcantara Borba (2009)
Fatigue can be defined as the inability to maintain the power output needed to perform a task and it is a mechanism of protection for the biological functions. It acts as a modulator of both the duration and the intensity of effort during exercise. High body temperature is accepted as being one of the important mechanisms leading to decreased ability to maintain the level of exertion. Clothing represents a barrier between the skin and the environment and it can affect heat exchange. The aim of the present study was to compare the effects of wearing different types of clothing (fabric and colour) on physical performance capacity during a 10-km race under the sun light. Six male (age: 30 + 4 years; height: 1.78 ± 0.05m; weight: 75.9 ± 9.6kg; V02max: 45.2 ± 2.4mL/kg.min) and six female volunteers (age: 25 ± 6 years; height: 1.64 ± 0,04m; weight: 58.0 ± 3.8kg; V02max: 40.9 ± 2.4 mUkg.min) ran a fast possible the distance under sun with 3-min intervals after every other 2-km. The 5 experimental situations were running: wearing no shirt; white polyester shirt; black polyester shirt; white cotton shirt and black cotton shirt, on a randomized and crossed order, 2 to 7 days apart. The WBGT for the female group (24.9±1.9 to 27.5±3.6°C) was higher (p<.05) than that of the male group (23.1 ±2.2 to 24.0±2.4° C). The type of clothing did not alter racing speed, core temperature, skin temperature, heart rate and local sweating sweat rate of males and females. Total sweating rate of the female was higher (p<.05) when they wore white cotton shirts. The temperature of the black cotton shirt was higher (p<.05) than that of the white polyester shirt. The perceived exertion of the male was lower (p<0,05) when they wore white polyester shirt compared to other shirts and in the female perceived exertion was higher (p<0,05) in the black cotton shirt compared to polyester shirt and wearing no shirt. The racing speed was steady during the first 4 km, decreased from the 4"^ to the 6'^ km and remained unchanged thereafter. Body temperature and heart rate increased mainly at the beginning of the race. The reduction in speed of the race was correlated with reduction rate body accumulation (r=.910 male; r=.988 female) We have concluded that the type of clothing did not change the race speed and the thermoregulatory responses of males and females during a self-paced 10-k race under sun light.